KONSEP TOLERANSI DALAM ISLAM DAN IMPLEMENTASINYA DI MASYARAKAT INDONESIA - Ni’maturrodiyah; Sunarno; Khoirul Fallah Setiawan; Putri Sekarwangi; Rizal Maulana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Tolerance is a noble value that is highly emphasized in Islam. The concept of tolerance in Islam is known as al-tasamuh, which has a broad meaning, namely mutual respect, respect for differences, and peaceful coexistence with others, both fellow Muslims and non-Muslims, the concept of tolerance in Islam has several basic principles, namely: al-hurriyah fi al-i'tiqâd (freedom of belief), al-insâniyyah (human values), and al-wasathiyyah (moderate). This research aims to examine the concept of tolerance in Islam and how this teaching can be applied effectively in Indonesian society. This research is a literature study, which is an in-depth research method to analyze and investigate relevant literature in a particular field of knowledge or topic. The paper explains that tolerance between communities can be achieved by incorporating the concept of tolerance in Islam. In addition, it can explore the various challenges faced in implementing tolerance as well as strategies that can be used to overcome obstacles that exist in society, so as to create tolerance in Islam that is mutually understanding and respectful between human beings. Keywords: Tolerance, Islam, Society